Agent based prototype for interoperation of production planning and control and manufacturing automation - Lima, Rui M. (2007)
This work describes a model for distributed dynamic Production Planning and Control (PPC) agent based system, which includes interoperation with manufacturing automation. It is presented a demonstration prototype involving distributed software agents and industrial equipment integration, which implements part of the developed model functionalities. Clients can send orders, and resources may apply for those orders fulfilment. Resources with orders allocated to, start automatically the required manufacturing operations. The prototype was implemented integrating several tools, including Lab VIEW and LEGO Mindstorms components. This is useful to validate the integration, proposed by the dynamic PPC model, between production planning processes and manufacturing execution operations.